The Influence of Digital Marketing Capability and Product Innovation in Marketing Performance: Study on Food and Beverage MSMEs in Surabaya - Kamaruzzaman, Muhammad Iqbal; Indarwati, Tias Andarini (CV ODIS, 2023)
MSMEs are one of the sectors that make the largest contribution to the GDP of the Republic of Indonesia, which is 60.5%. The number of SMEs every year is always increasing. However, the magnitude of the contribution and the increase in the number of MSMEs is not in line with the data which states that MSMEs experienced a decline in sales in 2020 of 94.69%, where the biggest decline was experienced by MSMEs that ran their business offline. Based on this phenomenon, this study aims to determine the effect of digital marketing capabilities and product innovation on marketing performance in MSMEs. This research is a quantitative research with a questionnaire as a research instrument which was distributed to 131 respondents using a purposive sampling technique. Data processing in this study used multiple linear regression analysis which was processed with SPSS 25. The results of the research show that digital marketing capabilities and product innovation have a positive and significant influence on marketing performance in food and beverage MSMEs in the city of Surabaya.